Unique Double-Stranded Fragments of Bacteriophage T5 DNA Resulting from Preferential Shear-Induced Breakage at Nicks - Hayward, Gary S. (1974)
Nicks within one strand of the bacteriophage T5 DNA molecule act as “ weak points” for a novel kind mechanical breakage that can be utilized for “dissecting” the genome. The products from sheared T5(+) DNA include five unique double-stranded segments of the molecule and various combinations of adjacent segments. These specific fragments are not obtained after repair of the nicks with DNA ligase (EC 6.5.1.1). The duplex fragments and most of their single-stranded components have been separated, identified, and mapped by means of agarose gel electrophoresis. Even the complementary strands of the unique fragments separate in agarose gels; hence, there are now three useful classes of DNA fragments available from T5: the natural r-strand fragments, their complements from the normally intact l strand, and the corresponding duplex segments. By summing the apparent molecular weights of their single-stranded components, the unique duplex fragments from T5(+) DNA can be assigned molecular weights of approximately 6 × 10(6) (A), 8 × 10(6) (B), 11 × 10(6) (C), 27 × 10(6) (D), and 30 × 10(6) (E) from left to right along the genome. The most abundant overlapping fragments are segments AB (14 × 10(6)) and ABC (26 × 10(6)). Differences in the number and relative positions of nicks within two distinct groups of heatstable deletion mutants [represented by T5st(O) and T5b3] account for the large differences observed in their patterns of breakage products.